Pharmacological profile of encounter-induced hyperactivity in isolation-reared mice. Issue 7 (October 2015) - Hasebe, Shigeru; Ago, Yukio; Nishiyama, Saki; Oka, Satoshi; Hashimoto, Hitoshi; Takuma, Kazuhiro; Matsuda, Toshio
Abstract : We have recently found that isolation-reared mice show hyperactivity during an encounter with an intruder. However, it is not known whether encounter-induced hyperactivity may model some aspects of psychiatric disorders. The present study examined the pharmacological profile of encounter-induced hyperactivity in isolation-reared mice. Encounter-induced hyperactivity was reduced by acute administration of various antidepressants including the tricyclic antidepressant desipramine (10 mg/kg), the selective serotonin (5-HT) reuptake inhibitors fluvoxamine (10 mg/kg) and paroxetine (10 mg/kg), the 5-HT/noradrenaline reuptake inhibitors venlafaxine (10 mg/kg) and duloxetine (10 mg/kg), the antipsychotic drug risperidone (0.01 mg/kg), the 5-HT2 antagonist ritanserin (1 mg/kg), and the glucocorticoid receptor antagonist RU-43044 (30 mg/kg). The α2 adrenoceptor agonist clonidine (0.03 mg/kg) and the 5-HT4 receptor agonist BIMU8 (30 mg/kg) also reduced encounter-induced hyperactivity. The effect of desipramine was blocked by the α2 adrenoceptor antagonist idazoxan (0.3 mg/kg). The effect of fluvoxamine was blocked by the 5-HT4 receptor antagonist GR125487 (3 mg/kg), but not the 5-HT1A receptor antagonist WAY100635 (1 mg/kg), the 5-HT3 receptor antagonist azasetron (3 mg/kg), or the 5-HT6 receptor antagonist SB399885 (3 mg/kg). The effect of venlafaxine was blocked by the simultaneous administration of idazoxan (0.3 mg/kg) and GR125487 (3 mg/kg), but not by either compound alone. These findings suggest that encounter-induced hyperactivity in isolation-reared mice is a robust model for testing the pharmacological profile of antidepressants, although the range of antidepressants tested is limited and some nonantidepressants are also effective. The present study also shows a key role of α2 and 5-HT4 receptors in the antidepressant effect in this model.